Rational Unified Process as a Software Development Method in Decision Support Systems Design with Simple Additive Weighting in Determining Priority Rehabilitations of Classrooms - Willy Prihartono; Sri Farida Utami (JURNAL SISFOTEK GLOBAL, 2023)
Rational Unified Process (RUP) as a development method in Decision Support System (DSS) is suitable for decision-making processes due to its possibility to show iterative and incremental processes in RUP. The decision-making process takes several phases, which are the intelligence phase, the design phase, the choice phase, and the implementation phase. In Decision Support System has many management models. Simple additive weighting (SAW), also known as the weighted summing method, is used as a management model in this paper. The basic concept of the SAW method is to find the weighted sum of performance ratings for each alternative on all attributes. The RUP Approach, which has an iterative and incremental nature, is expected to become a solution in a decision support system. The RUP project has four phases: inception, elaboration, construction, and transition to the software product. RUP divides software development into a number of "disciplines" that are iterations or phases. Each discipline has associated goals and outputs that are accomplished through planned activities. Complete documentation for every stage of development is also emphasized by RUP. The fundamental of RUP are architecturally based approaches, iterative and incremental development, object-oriented modeling, risk management, and a focus on software quality. Collaboration between the software development team and relevant stakeholders is also encouraged by this methodology.